PELATIHAN VIDEO PEMBELAJARAN BERBASIS APLIKASI VN PADA GURU SEKOLAH MENENGAH ATAS - Wildan Aji Saputra; Irfan Fatkhurohman; Tegar Roli Anugrafianto (Unity Academy, 2023)
This service activity aims to improve the skills of high school (SMA) teachers in the field of video editing, especially for video editing applications using mobile devices or smartphones. VN video editor is a video editing application specifically designed for mobile devices or smartphones. This application is very suitable for high school teachers who want to do video editing anywhere and anytime via the smartphone they use. Currently, the use of learning media via video is very widely used and implemented in almost all schools and even universities. This is used as a community service activity in the form of training provided to high school teachers. The aim of this service is to train teachers in Purwokerto who do not have a scientific background in information technology and are required to carry out teaching and learning activities using audio-visual methods. As a result of the evaluation of this training activity, teachers have been able to make learning videos using the VN video editor tool to support their students so that learning activities become more enjoyable and less monotonous.